Impact of Endocrine Disrupting Chemicals (EDCs) on Male Health: A Comprehensive Literature Review - Bezara, Damian; Żak, Agata; Adamczyk, Aleksandra; Gut, Michał; Ważny, Maria; Toporowska-Kaźmierak, Joanna; Gancarz, Agnieszka; Sowińska, Marta; Tworek, Miłosz; Banasik, Mateusz (Journal of Education, Health and Sport, 2026)
Background: Endocrine disrupting chemicals (EDCs) impact human health by modulating endogenous hormones. While linked to metabolic, oncological, and reproductive disorders, literature often focuses narrowly on specific aspects of male health. Objective: To provide a holistic analysis of EDC impact on male health (Homo sapiens) based on literature from 2000–2025, excluding in vitro and animal models. Methods: A three-stage review of PubMed identified 51 records. After rigorous screening, 34 high-quality studies (systematic reviews, meta-analyses, and RCTs) addressing effects on the living male organism were synthesized. Results: EDC impact is multidirectional and highly dependent on exposure windows. The prenatal period is critical for testicular cancer development and adult semen quality. Exposure to BPA, phthalates, and PAHs correlates with increased risk of ADHD and autistic behaviors in boys. Metabolically, PFAS and bisphenols correlate with abdominal obesity and diabetes, showing strong sexual dimorphism. Pathophysiological mechanisms include disruption of the HPG/HPT axes, oxidative stress, and epigenetic modifications. Conclusions: EDCs are a systemic risk factor extending far beyond reproduction. Key research barriers include methodological heterogeneity and the neglect of the "cocktail effect." There is an urgent need for standardized, longitudinal prospective studies starting from the prenatal period to assess real-world anthropogenic impacts.